Strength-based faithfulness and the sibilant /s/ in Italian - Baroni, Antonio (Yearbook of the Poznan Linguistic Meeting, 2014)
Notwithstanding the primacy of the CV syllable, a number of languages allow for more complex types of syllables. In particular, word-initial consonant clusters are particularly challenging for any phonological theory. In this paper it is argued that obstruent clusters may be the result of casual speech processes where the most salient/ frequent phonemes and features occurring in most pronunciation variants of a word are preserved. As a result, sibilants, being acoustically salient, tend to occur more often than other obstruents as the first member of word-initial obstruent clusters. A framework couched in Optimality Theory is presented, where a subfamily of faithfulness constraints refer to strength values stored in the underlying representation. The more salient and/or frequent a phoneme/feature is, the higher the strength value assigned to it. Finally, a number of languages are compared, arguing that their phonotactic differences may be due to the different ranking of markedness constraints and MAX-STRENGTHVALUE constraints.